Consumer’s attitude towards counterfeit products among students in Universiti Malaysia Kelantan City Campus - Khidarshini Ravidaran; Muhammad Azam Raizal Shakroni; Muhammad Khalis Rafie; Muhamad Shahrin Muhamad Ali Hassan (2019)
This study is to investigate the customers’ attitude towards counterfeit goods among students in Universiti Malaysia Kelantan, City Campus. The nature of this research is researching which factors that influence the customer’s attitude towards counterfeit products among students in UMK City Campus. In conducting this research, we found out that there are four independent variable (IV) which is status consumption, integrity, personal gratification and purchase intention that can be relate to our dependent variable (DV). Our objectives in this research to identify the status consumption influence on consumer’s attitude towards counterfeit products among students in Universtiti Malaysia Kelantan (UMK), City Campus, to examine the integrity influence on consumer’s attitude towards counterfeit products among students in UMK, City Campus, to determine the personal gratification influence on consumer’s attitude towards counterfeit products among students in UMK, City Campus, to identify the purchase intention influence on consumer’s attitude towards counterfeit products among students in UMK, City Campus, and the last objective is To investigate the most important factors that influence on consumer’s attitude towards counterfeit products among students in UMK, City Campus. A quantitative research was used in this research. To collect the data, 361 respondents were evaluated through a structured questionnaire which was targeting the UMK City Campus students. The data was analysed using Statistical Package for Social Sciences (SPSS) version 25.0. The Pearson’s Correlation test was used to test the relationship between independent and dependent variables. Results were illustrated in tables and charts. Results showed that there was positive significant relationship between status consumption, integrity, personal gratification and purchase intention towards counterfeit products among students in UMK City Campus. The final data shows that purchase intention had the most factors influence on consumers attitude towards counterfeit products among students in UMK city campus with the correlation coefficient of 0.756. Our research will give benefits to a several parties. The first party that are going to get benefits are the industry itself. Industry can identify the reason the consumers are preferred counterfeits products than the original products. The second party that get benefits from the research are the customers. This is because the customers can buy or own the products with a moderate quality with lower price. They can make a choice either to buy the original products or the counterfeits products. The last party that get the benefits are the researchers. This study could be a reference to the future researcher that are going to conduct a research in the same field. This study is also affected to the manufacturer of counterfeit products because people may rethink before buying a counterfeit product after read this thesis and there will be a positive impact to the original products manufacturer because there will be an increase of a demand after people read this thesis.